Advances in Diagnosis of Progressive Pulmonary and Disseminated Coccidioidomycosis. (28th February 2020) - Kassis, Christelle; Durkin, Michelle; Holbrook, Eric; Myers, Robert; Wheat, Lawrence
Abstract: Background: Antibody detection is the main method for diagnosis of coccidioidomycosis, but it has limitations. The Coccidioides antigen enzyme immunoassay is recommended for testing cerebrospinal fluid in suspected meningitis. Reports on urine and serum antigen detection evaluated small numbers of patients who were mostly immunocompromised. The purpose of this study was to assess the accuracy of combined antibody and antigen detection for diagnosis. Methods: A retrospective study, including all patients in whom Coccidioides antigen detection in serum was performed between January 2013 and May 2017, was conducted at Valleywise Health Medical Center (formerly Maricopa Integrated Health System). Sensitivity and specificity of antigen and antibody were evaluated in 158 cases and 487 controls. Results: The sensitivity of antibody detection by immunodiffusion (ID) was 84.2%. The sensitivity of antigen detection was 57.0% if both urine and serum were tested and 36.7% if urine alone was tested. The sensitivity of combining antigen and ID antibody detection was 93.0%. The sensitivity of urine and serum antigen detection was 55.4% in proven and 58.7% in probable cases, 79.1% in disseminated and 41.6% in pulmonary cases, and 74.7% in immunocompromised and 40.0% in immunocompetent patients. Specificity was 99.4% for antigen detection and 96.5% for ID antibody detection. Diagnostic accuracy was 95.4% for ID antibody and antigen detection, 93.6% for ID antibody alone, and 89.1% for pathology or culture. Conclusions: These findings support combined antibody and antigen detection for diagnosis of progressive coccidioidomycosis. The diagnosis may have been missed if antigen detection was not performed. Abstract : Combined Coccidioides antigen and antibody testing is the most sensitive method for diagnosis of progressive disseminated or pulmonary coccidioidomycosis. Sensitivity of antibody detection by immunodiffusion or enzyme immunoassay is inadequate for screening. More-sensitive antibody testing methods are needed.